TRANSFORMATION OF GENDER COMPONENTS OF MODERN FAMILY EDUCATION - E. M. Luschenko (Научный вестник МГТУ ГА)
The article is devoted to transformation of the institution of parenthood, as expressed in changing the structure and function of the family. The problems of feminization and masculinization in the process of family up-bringing have been revealed. The tendencies to development of the institution of parenthood, as well as various factors that influenced the transformation of the institution of parenthood have been studies.